Upaya Peningkatan Kompetensi Guru SMP 2 Cangkringan dalam Menulis Karya Ilmiah: Indonesia - Tanjung, Sumekar (Jurnal Abdimas Madani dan Lestari (JAMALI), 2024)
The result of author observations, the most of the teacher's activities at SMP 2 Cangkringan are more oriented towards the mission of education and teaching in the classroom. Meanwhile, scientific vision and mission in the form of scientific writing and publication are often neglected. The implications of this fact, the writing and publication of scientific papers among teachers is still a cause for concern. The solution offered is to provide training in writing scientific papers for Cangkringan 2 Middle School teachers. The output target of this dedication is in the form of training services in the form of information related to writing scientific papers and publishing scientific articles. Through the community service activities that have been carried out, three things have been improved, namely deepening teacher knowledge about scientific writing, introducing and promoting the activity of writing scientific articles in journals to increase professional competence and motivating teachers to start publishing scientific papers in the form of scientific articles in journals. The method used is the method of lectures, discussions, and questions and answers. The result of implementing this community service activity is to provide an understanding of scientific writing, the reasons why teachers have to make scientific papers, the concept of scientific writing, and the process of writing scientific papers. Furthermore, the teachers received material on how to publish scientific papers and their stages.